Debriefing in the simulation contexts - Lobão, Catarina (2014)
The debriefing has accompanied the development of the simulated training contexts of health and has been identified as an important clarification and consolidation step of learning experiences. The debriefing is identified as a strategy that allows the reviewing of a simulated experiment in which participants explore, analyze and synthesize their action, thought and other information that can enhance their performance in real contexts (...)